THE STUDENT WITH HIGH SKILLS/GIFTEDNESS IN RIVERSIDE SCHOOL IN AMAZON - Oliveira Ferreira, Jose Adnilton; Carbone Carneiro, Relma Urel [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
In this study we investigated the student with high skills/giftedness in a riverside School in Amapa's Amazon with possibility of inclusion in school? A research based on the qualitative approach was conducted, from the following problem question: How has the inclusion of a student with high skills/giftedness at a riverside school in the city of Mazagao in the state of Amapa been taking place? The study aimed to analyze the inclusion process of students with high skills/giftedness from the 1st to the 5th grade of elementary School. The locus of the research was a riverside school located in the municipality of Mazagao in the state of Amapa. For data collection, semi-structured interviews, observation and photographic recording were performed. The participants of this research were a teacher of the student's class with high skills/giftedness, a teacher of specialized educational attendance, a student with high skills/giftedness, a pedagogical coordinator and the school principal. The collected data was analyzed from the definition of the Aprioristic Category: school inclusion, as well as other intermediate categories and final categories that, in the case, are the non-aprioristic ones that emerged from the theoretical framework adopted in the research and Empirical research. As a result, this study brings significant theoretical and practical contributions to the process of inclusion of students with high skills/giftedness in this riverside School in the Amapa's Amazon. The results showed that there are difficulties in the process of inclusion of this public related to various aspects such as the formation of teachers and of the entire school team, infrastructure, the organization of classrooms, among others, as well as, demonstrate the importance of research in this universe to strengthen theoretical-practical questions related to inclusion.
Keywords: School inclusion; High abilities/giftedness; Amapa's Amazon; Riverside education